Transforming Burundi's coffee sector through strategic value chain investments. Issue 3 (13th November 2017) - Bro, Aniseh; Clay, Daniel C.
Abstract : Purpose: The purpose of this paper is to examine the early stages of the transition to specialty coffee in Burundi and the role of an agribusiness support program as a catalyst for this transition. Design/methodology/approach: This study uses two years of panel data (2007 and 2012) to analyze changes in technology adoption among coffee washing stations (CWSs) and how the adoption of improved technologies affects coffee quality. Findings: Programmatic investment in Burundi's coffee value chain resulted in a significant shift in adoption of processing technologies by CWSs. Producers who processed at these stations saw a significant increase in the quality of their coffee and forged sustainable trade relationships with international buyers. Research limitations/implications: Future research should investigate the incentives and barriers of producers to invest in production boosting practices. Originality/value: This is one of the first empirical papers that analyzes Burundi's transition from ordinary to specialty coffee and how programmatic investments in improved technologies has helped to make the change possible.